Experience in the implementation of the electronic information and educational environment in the practice of a scientific and pedagogical worker of a university - Marina Vladimirovna Vakulenkova (Вестник Майкопского государственного технологического университета)
Currently, educational institutions are actively transitioning educational activities to the use of an electronic information and educational environment through the introduction of a wide range of information and telecommunication technologies in the field of higher education. This leads to global changes in the conditions for the functioning of higher educational institutions, which makes it necessary to revise traditional approaches to the organization of the educational process. The basis of this process is not only a change in the educational process, but also the improvement of the management of this process and the university as a whole through the creation of an electronic information and educational environment.The problem of the research is to reveal the experience of implementing the electronic information and educational environment in the practice of a scientific and pedagogical worker of a university. The purpose of the research is to substantiate the effectiveness of using the electronic information and educational environment of a university in the educational process. The research methods are analysis, survey, generalization, description, forecasting. The research results are the concept of "electronic information and educational environment" has been disclosed; the basic resources of the electronic information and educational environment of higher educational institutions have been described; the experience of using the Moodle platform in the educational process in the direction of preparation 44.03.02 Psychological and pedagogical education, focus: "Psychology and Pedagogy of Primary Education" has been presented; the results of an online survey of students on the advisability of using an electronic information and educational environment in the educational process have been shown.Key conclusions: the electronic information and educational environment of the university is a set of electronic resources that ensure the synchronous interaction of all participants in the educational process of the educational institution; the basic resources of the electronic information and educational environment of higher educational institutions are the official website of the educational organization, online learning platforms, automated testing systems, portals / teams of deans, departments, curators, teachers, students, etc.; An online survey of students has revealed the interest of students in the use of electronic resources in the educational process.